ĐẶC ĐIỂM QUẶNG HÓA VÀ KHOÁNG VẬT CÁC MỎ KẼM CHÌ KHU VỰC LÀNG HÍCH - Cẩn, Phạm Ngọc; Anh, Trần Tuấn; Hòa, Trần Trọng; Dung, Phạm Thị; Phượng, Ngô Thị; Hùng, Trần Quốc; Niên, Bùi Ấn; Ý, Nguyễn Viết; Hiếu, Trần Văn (Vietnam Journal of Earth Sciences, 2011)
Chemical and mineralogical characteristics of Zn-Pb ores in Lang Hich areaLang Hich ore deposit consisting of 6 mining places (West Metis, East Metis, Hang Chua, Bac Lau, Mo Ba - 1Aoven, Mo Ba - 1B) was discovered in 1905 and has been exploited since 1913. Anually, the mine have been exploited ~20000 T, inspite of lacking detail investigation in mineralogy and chemistry of ores.Two mineral assemblages have been clafsified in Lang Hich deposit as followed : 1) pyrite-galenite-sphalerite (Metis,Mo Ba), 2) galenite-sphalerite (Bac Lau, Hang Chua). Basically, sphalerites, have low Fe, In contents ; Bi is medium ; Mn and Cd is high, especially, Cd have very high content. While galenite contains Ag at economical value, besides, the presence of Sb is recored. Other investigation also shows the existing of tetraedrite group, an Ag bearing mineral group, and bournonite, a Sb bearing mineral.